Analisis Kompetensi Profesional Guru Dalam Penerapan Pembelajaran Tematik Integratif Di Kelas II Dan IV SD Negeri 1 Simo - Mahardika, Dian Sari, Drs. Suwarno, SH, M.Pd (2017)
This study aims to find out more about the professional competence of teachers in the application of thematic integrative learning in class II and IV SD Negeri 1 Simo who is one of the elementary school curriculum pilot project for 2013. This study is a qualitative type of research phenomenology. The research subject is class II and IV teacher, grade II and IV, as well as the principal. Data collected through observation, interviews, and documentation. The instrument of this research using observation sheet and questionnaire. Data were analyzed using data reduction, data display, and conclusion. Test the validity of the data using triangulation techniques, and check. Results of research grade II teacher and classroom teacher IV was prepared in the implementation of thematic integrative learning. Master class II and IV have mastered the professional competence in the application of thematic integrative learning. Principals, teachers, facilities and prasanana, the environment around SD Negeri 1 simo supports in a Learning thematic integrative.